2014
DOI: 10.1016/j.cub.2014.05.024
|View full text |Cite
|
Sign up to set email alerts
|

A Circannual Clock Drives Expression of Genes Central for Seasonal Reproduction

Abstract: Animals living in temperate zones anticipate seasonal environmental changes to adapt their biological functions, especially reproduction and metabolism. Two main physiological mechanisms have evolved for this adaptation: intrinsic long-term timing mechanisms with an oscillating period of approximately 1 year, driven by a circannual clock [1], and synchronization of biological rhythms to the sidereal year using day length (photoperiod) [2]. In mammals, the pineal hormone melatonin relays photoperiodic informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
100
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 42 publications
(75 reference statements)
8
100
3
6
Order By: Relevance
“…For the former, history-dependent effects at the level of PT TSH production appear to be important (26,27), whereas, for the latter, echoing the present study, large increases in dio2 expression are associated with a slight rise in PT TSH expression (26). Similarly, European hamsters maintained in constant LP show sustained cycles in PT TSH and hypothalamic dio2 expression, correlated with changes in physiological status (28). Collectively, these observations suggest that the internal representation of calendar time (i.e., circannual timekeeping) may emerge through photoperiodic history dependence both in the PT response to photoperiod and in the tanycyte response to the PT.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…For the former, history-dependent effects at the level of PT TSH production appear to be important (26,27), whereas, for the latter, echoing the present study, large increases in dio2 expression are associated with a slight rise in PT TSH expression (26). Similarly, European hamsters maintained in constant LP show sustained cycles in PT TSH and hypothalamic dio2 expression, correlated with changes in physiological status (28). Collectively, these observations suggest that the internal representation of calendar time (i.e., circannual timekeeping) may emerge through photoperiodic history dependence both in the PT response to photoperiod and in the tanycyte response to the PT.…”
Section: Discussionsupporting
confidence: 65%
“…(B) The pars tuberalis transduces melatonin signal duration into production of TSH. No history dependence was observed at this level in the present study, but effects have been reported in other seasonal paradigms (27,28) and may contribute to ellipsis in the encoded response to photoperiod. (C) Strong history dependence is seen in the hypothalamic response to TSH, giving a history-dependent internal representation of calendar time.…”
Section: Discussioncontrasting
confidence: 45%
“…L'horloge circannuelle régule notamment l'expression de la TSH qui, via l'hormone T3 hypothalamique, transmet l'information circannuelle vers des structures centrales contrôlant de grandes fonctions biologiques, incluant probablement l'hibernation. L'horloge de la pars tuberalis a également été impliquée dans le contrôle circannuel de la [3]. Des hamsters mâles ont été privés de repères saisonniers en les exposant à une photopériode fixe et en supprimant la synthèse de mélatonine par pinéa-lectomie.…”
Section: Mécanismes Centraux De L'horloge Circannuelleunclassified
“…Pour émerger de leur terrier au jour dit, en l'absence de toute information extérieure, les animaux doivent disposer d'un système endogène de mesure du temps qui sonne le signal du réveil interne. Ce système fait intervenir une horloge circannuelle (circa : environ ; annus : an) endogène qui contrôle la synthèse de protéines hépatiques impliquées dans le réveil métabolique [2], et des mécanismes neuroendocriniens qui activent la reproduction [3].…”
unclassified
See 1 more Smart Citation